Perancangan ATM Raskin Berbasis RFID dan Internet of Things (IoT) untuk Masyarakat Tidak Mampu - Syafrie Syahriel; Adi Prijuna Lubis; Rizky Fauziah (J-Com (Journal of Computer), 2021)
Abstract: Raskin is a government subsidy program in the form of food assistance, distribution of rice given to poor households. For the management or implementation of the distribution of Raskin, it has been determined according to the data obtained from the village. However, for the distribution of Raskin, the village has difficulties in weighing rice and re-collecting data on the people who get Raskin and must also distribute the community in each hamlet, so to make it easier for the distribution of Raskin rice, the researchers designed a Raskin ATM to help the village and the underprivileged, and to make the distribution easier. young to take the rice. Raskin ATM designed using Radio Frequency Identification (RFID) and Internet of things (IOT). Rice ATM which will be placed in the village office or village hall office. This tool makes it easier to create reports that are already stored in the system that was created. Every transaction on an ATM machine will send information to the person in charge of the ATM machine, namely the Lurah or Village Head       Keywords: Rice ATM; radio frequency identification; raskin; atm at the Balai's office village.  Abstrak: Raskin merupakan program subsidi pemerintah berupa bantuan pangan, penyaluran beras yang diberikan kepada rumah tangga yang tidak mampu. Untuk pengelolaan atau pelaksanan dalam pembagian raskin sudah ditentukan sesuai dengan data yang di dapat dari desa. Namun untuk pembagian raskin tersebut desa  kerepotan dalam penimbangan beras dan pendataan ulang masyarakat yang mendapatkan raskin dan juga  harus membagikan masyarakat di setiap dusun,  jadi untuk mempermudah dalam pembagian beras raskin peneliti merancang sebuah ATM Raskin untuk membantu pihak desa dan  masyarakat kurang mampu, dan untuk lebih muda untuk pengambilan beras tersebut. ATM Raskin yang dirancang menggunakan Radio Frekuensi Identifikasi (RFID) dan Internet of things (IOT). ATM beras yang nantinya ditempatkan di kantor kelurahan atau kantor balai desa. Dengan adanya alat ini mempermuda untuk membuat laporan yang sudah tersimpan didalam sistem yang dibuat. Setiap transaksi pada mesin ATM akan mengirimkan informasi kepenanggung jawab mesin ATM yaitu Lurah atau Kepala Desa. Kata kunci: ATM Beras; Radio Frekuensi Identifikasi; Raskin; ATM Kantor Balai Desa.